Rapor Pendidikan Indonesia: Quo Vadis Kualitas Pendidikan Indonesia? - Dwi Shintia; Masduki Asbari; Fadhila Khairunisa; Nurul Azizah (Journal of Information Systems and Management (JISMA), 2023)
The aim of this study is to determine how to improve the quality of education in Indonesia by providing integrated and data-based information to education units and local governments for reflection and improvement. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from the Indonesian Ministry of Education and Culture's Youtube channel entitled "Merdeka Belajar Episode 19: INDONESIAN EDUCATION RAPOR" presented by him. The results of this study explain that Indonesian Education report cards help education units and local governments identify education challenges in education units and become material for reflection so that they can develop education improvement plans more precisely and based on data, as well as presenting the results of national assessments and other data regarding learning outcomes. Education units into an integrated display and information about quality and inequality in a simple, easy-to-understand manner, integrating various education data to help education units and education offices identify achievements and the roots of problems.